Cosmopolis in the pre-modern epoch on the border of the Western and Eastern cultures: multilingualism and limits of transferability (on Caffa’s materials of the 13th–15th centuries) - Emanov A.G. (Золотоордынское обозрение)
Objective: To investigate the problem of the terminological precision of the most relevant qualities possessed by cosmopolis in the pre-modern world where the representatives of Western and Eastern faith acted equals in various written and spoken languages. Research materials: The “Codex Cumanicus” composed in Caffa at the turn of the 13th–14th centuries; the lexis of medieval urbanism in three languages (Latin, Persian, and Comanian) selected from it; “Libellus de notitia orbis” of Iohannes de Galonifontibus with a description of multilingual Caffa from the early 15th century. Results and novelty of the research: From the “Codex Cumanicus” was first isolated the lexis of medieval urbanism, dispersed throughout four semantic fields: representation of cosmopolis in the physicality, legally, the sociocultural data, and the ethical community. The representation of cosmopolis in the physicality found untranslatability to eastern languages such Latin terms as “murus”, and “vacuum”, calling attention to essential attributes of urban physis – stone walls, and public places. The representation of cosmopolis in the legally data proved the failure to communicate such thing as a “libertas”, the key characteristic of a free city; the Latin term “civitas”, a community of citizens, was adapted in Coman language only through Sogdian analogy of “känd”. The concept “lex”, law, was perceived only through the Jewish approach of “ˈtorə”. The representation of cosmopolis in the sociocultural data did reflect the richness of terms which represented the merchants, traders, bankers, artisans, warriors, and those in the service, education, and entertainment industries; most of them entered the language as a borrowings from Persian and Arabic. The representation of cosmopolis as ethical community explained the rethinking any archaic thought forms of the earlier polytheistic mind moving toward the monotheistic idea; the central concept of Western culture “Deus”, God, was reinterpreted in the most distant Eastern cultures as “Tengri” like the designation used earlier for the supreme sky deity of all Asian nomads; the universal theories for both West and East about the four elements and four bodily fluids reflected the relation between the world and man, as macrocosm and microcosm, really integrated citizens of different faiths and languages into the ethical community. This research uses the cognitive science and mental mapping methods. The first allows one to inquire on the terms, ideas, linguistic units, verbal codes in which was treated the cosmopolis in the pre-modern world. The second makes it possible to visualize a distribution of lexical triads according to the degree of positivity / negativity, nearness / distance in transmitting meanings from Latin in Eastern**.